1988
DOI: 10.1037/0022-006x.56.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing effects of pretreatment measures on cancer chemotherapy nausea and vomiting.

Abstract: This study explored the sensitizing effects of pretreatment assessment on posttreatment chemotherapy nausea and vomiting and the interactive effects of personal dispositions for information seeking. Seventy oncology outpatients were recruited from oncology waiting rooms prior to receiving scheduled chemotherapy. Half of the patients were asked to complete an inventory about the severity of side effects that they had experienced following their most recent treatment session (experimental condition) and half wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 16 publications
1
29
2
Order By: Relevance
“…For example, patients that received the information correctly answered 95% of the questions in the quick quiz, and all patients trained in relaxation reported practising relaxation at home, as well as after the surgery. We were unable to detect the interactive effect in contrast to other investigations (e.g., Gard et al, 1988;Efran et al, 1989;Lerman et al, 1990;Gattuso et al, 1992). Several reasons may account for this lack of support for the hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, patients that received the information correctly answered 95% of the questions in the quick quiz, and all patients trained in relaxation reported practising relaxation at home, as well as after the surgery. We were unable to detect the interactive effect in contrast to other investigations (e.g., Gard et al, 1988;Efran et al, 1989;Lerman et al, 1990;Gattuso et al, 1992). Several reasons may account for this lack of support for the hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…On the basis of this discussion, it is important to consider the extent to which monitoring activities are associated with psychological distress. Previous research has reported increased levels of physiological, subjective and behavioural arousal in ‘monitors’ in other uncontrollable threatening situations ( Miller 1980, Phipps & Zinn 1986, Gard et al . 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, researchers have indicated a possibility that patients' coping styles (not examined in this study), may serve as a mediator between perceived severity of symptoms and anxious mood during chemotherapy. [29][30][31] In the mediating analyses examining the link between number of symptoms reported and depressed mood, we found that making symptom attributions to illness was important in reducing the association between number of symptoms reported and depressed mood. This only occurred, however, in combination with consequence beliefs, which, on their own, partially mediated the relationship.…”
Section: Commentmentioning
confidence: 99%